ANALISIS PERILAKU INSTABILITAS PEREKONOMIAN INDONESIA: APLIKASI VECTOR ERROR CORRECTION MODEL - Andi Irawan; Perry Warjiyo (Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
In general the aim of this study is to investigate short-run relationships among macroeconomy, international trade and agriculture in Indonesia. Under such circumstances, the specific goals of this research is to analyze which economic blocks that have most affected by instability, as well as producing instability in the economy. We apply the Vector Error Correction Model on monthly series data from 1993:01 to 2002:12. The main result of this study shows as follow: 1) that the asset financial and the commodity demand blocks the most producing instability in the economy. On the other hand, the export block producing the least instability to the economy. The finding suggest that government should concentrate attention on asset financial and the commodity demand blocks in stabilizing the economy, as they are major sources of instability of the economy. 2) To stabilize the commodity demand, it is also necessary to stabilize the financial market, as the assets demand block is the most contributor of the instability in the commodity demand block. In other words, money demand is the main source of instability. Because money supply is determined by government, the disequlibrium error measure the excess supply of money in the market. This suggest that monetary policy that reduces the disequlibrium error can help stabilize the economy.